Pembuatan Sistem Informasi Administrasi Untuk Kursus Mobil Berbasis Website dan Mobile - gunawan, willy wardhana; Budhi, Gregorius Satia; Andjarwirawan, Justinus (Jurnal Infra, 2014)
Car course center is a course center for people who want to learn to drive properly. Today there are many places that provide services course car. But for now this all transaction records are still using the manual system, so that all processes are less accurate recording. In addition to the monthly reporting process that is old and inaccurate, because it must calculate each transaction that occurs every day. Therefore we need a system based on information technology to improve the weaknesses of the old system.In the manufacture of the new information system, it is intended to be able to record income and expenditure transactions quickly and accurately. And can display monthly reports quickly and accurately to the owner of the car course center. Besides this new information systems it can make their own schedule tutoring participants registering through the website. Old systems analyze process by conducting a survey to the course car, and making DFD and ERD using power designer.From the results of the testing of this new information system it can keep records of income and expenses accurately, and course participants can register themselves through the course schedule website, and can display all the reports to the owner. The results of questionnaires completed by 5 people correspondent, application assessment showed 85% overall good.